CORRELATION OF F2-ISOPROSTANE WITH INTERLEUKIN-6 AND INTERLEUKIN-10 IN TRANSFUSION-DEPENDENT THALASSEMIA PATIENTS : A CROSS-SECTIONAL STUDY - Muhlisa, Nurul; Hernaningsih, Yetti; Wardhani, Puspa; Andarsini, Mia Ratwita; Ali Hasan, Zulfikar (Folia Medica Indonesiana, 2025)
Transfusion-dependent thalassemia (TDT)[-7pc]AU: Please Provide authors affiliations. is a condition in which patients require lifelong regular blood transfusions. However, regular blood transfusions carry a major risk of iron overload, which accumulates in the body and can trigger oxidative stress and chronic inflammation. Oxidative stress is characterized by an increase in reactive oxygen species (ROS), which can be assessed through the measurement of F2-Isoprostanes (8-iso-PGF2α). Excessive ROS affects cytokine production by inducing an inflammatory response, such as IL-6 and IL-10. This study aims to analyze the correlation between F2-isoprostane with Interleukin-6 and Interleukin-10 levels in TDT patients. This research was an observational analytical study with a cross-sectional design that involved 33 patient samples at Dr. Soetomo General Academic Hospital, Surabaya, from July to August 2025. The variables studied included F2-Isoprostane, IL-6, and IL-10 levels. F2-Isoprostane and IL-10 levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method (Isoprostane assay kit ELISA No. E-EL 47 0041 Elabscience and Human IL-10 kit ELISA No. E-EL-H6154 Elabscience). IL-6 levels were measured using the Chemiluminescence Immunoassay (CLIA) method (CLIA MAGLUMI IL-6 kit, Snibe). Data were analyzed by the Spearman correlation test. The results showed that the correlation coefficient (r) and significance values between F2-Isoprostane and IL-6 (p = 0.887; r = 0.026) indicated a very weak positive correlation, while IL-10 (p = 0.904; r = –0.022), showed a very weak negative correlation that was not statistically significant. This study demonstrates that there is no correlation between F2-Isoprostane levels, as a marker of oxidative stress, and IL-6 or IL-10, as markers of inflammation.